Clindamycin-resistant among Staphylococcus aureus: Investigation into phenotypic and genotypic profiles - Khursheed, Mariyam; Sulaiman, Maryam; Alhassan, Abdulrahman M.; Al Awad, Tameem H.; Ibrahim, Ahmed E.; Wilson, Godwin; Abdelrahaman, Hana A.; Eltai, Nahla O. (PLOS ONE, 2025)
Background Antimicrobial resistance (AMR), particularly methicillin-resistant Staphylococcus aureus (MRSA), is a pressing global health concern. These bacteria are increasingly becoming resistant to the most commonly available treatment options. As a choice, the macrolide lincosamide-streptogramin B (MLSB) is used, with clindamycin being the preferred drug. However, an alarming number of staphylococcal strains are developing resistance to MLSB. The resistance exhibits several phenotypes, including inducible MLSB (iMLSB), constitutive MLSB (cMLSB), and macrolide streptogramin B (MSB). One of the biggest challenges is the accurate detection of iMLSB in routine laboratory tests, as they appear erythromycin-resistant and clindamycin-sensitive unless the two antibiotics are placed adjacent to each other, which leads to clinical therapeutic failure. Method To achieve this, double disc diffusion (D test) was used to test iMLSB phenotypically. In addition, the genetic determinants were identified through singleplex PCR using specific primers to detect erm (A, B, C) and msr genes associated with the different phenotypes of MLSB resistance. Result Among 161 S. aureus isolates, 42 (26.1%) were erythromycin-resistant; 25 (15.5%) showed an iMLSB phenotype, and 16 (9.9%) displayed an MSB phenotype. One MRSA isolate expressing cMLSB phenotype. Genotypic analysis revealed a prevalence of ermC in 60% and msr in 40% of S. aureus isolates. Conclusion The D-test is a reliable method for identifying inducible clindamycin resistance in clinical diagnostics, to support antibiotic use and treatment stewardship in Qatar.